Biology, Genetic Diversity, and Ecology of Nitzschia acidoclinata Lange-Bertalot (Bacillariophyta) - Veronika B. Bagmet; Shamil R. Abdullin; Arthur Yu. Nikulin; Vyacheslav Yu. Nikulin; Andrey A. Gontcharov (Diversity, 2022)
The diatom Nitzschia acidoclinata is a widespread eurybiontic alga. There is little information on its life cycle properties and cardinal points. To fill this gap, we analyzed six N. acidoclinata clones from a range of habitats in Asiatic Russia regarding their genetic diversity, morphology, morphometry, geography, and ecology. A comparison of 15 N. acidoclinata rbcL sequences sampled across its relatively wide distribution area and contrasting habitats revealed no distinct genotypes in the species. We demonstrated that the valve morphology, their length, and the sexual activity of the investigated clones varied depending on the phase of their life cycle. In this species, abrupt size reduction was observed. It was revealed that N. acidoclinata reproduced by pedogamy, and its auxosporulation was season-dependent and observed in spring and autumn only. The mating activity in our clones was detected only when the cell size was reduced to 9–22 µm in length. The available data on sexual reproduction in the genus Nitzschia suggest that neither clades nor subclades comprise pedogamous or anisogamous taxa at the same time. However, isogamy could occur in the same clade with either pedogamy or anisogamy. These data provide a fundamental basis for the development of N. acidoclinata mass cultivation and long-term maintenance in culture technologies.